Debus: Tradisi Keagamaan dan Spiritualitas Islam di Banten - Muhammad Fadzli; Albarra Gilang Andika; Jullyandra Eka Putra; Ahmad Maftuh Sujana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Debus is one of the typical traditions and cultures of Banten that combines elements of art, religion and spirituality in one unit. The art of Debus began to be introduced around the 16th century which until now is still an artistic heritage in Banten so it is interesting when viewed in terms of the values contained in the art. This journal aims to examine the values contained in the Debus tradition in Banten and its relevance to Islamic teachings. This research is a qualitative research by combining two data acquisitions in the form of literature and field studies, this study found that the Debus art tradition contains several elements, such as art elements (martial arts movements), religious elements (reading solawat), and spiritual elements (tawakal and self-surrender).